2013
DOI: 10.3390/ijms140714214
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Weight Dependent Glucose Lowering Effect of Low Molecular Weight Chitosan Oligosaccharide (GO2KA1) on Postprandial Blood Glucose Level in SD Rats Model

Abstract: This research investigated the effect of enzymatically digested low molecular weight (MW) chitosan oligosaccharide on type 2 diabetes prevention. Three different chitosan oligosaccharide samples with varying MW were evaluated in vitro for inhibition of rat small intestinal α-glucosidase and porcine pancreatic α-amylase (GO2KA1; <1000 Da, GO2KA2; 1000–10,000 Da, GO2KA3; MW > 10,000 Da). The in vitro results showed that all tested samples had similar rat α-glucosidase inhibitory and porcine α-amylase inhibitory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 23 publications
2
40
0
Order By: Relevance
“…This is the first kind of study performed to determine the anti-diabetic activity and standardizing dose of chitosan and chitooligosaccharides (chitin-based derivatives) in treatment of diabetes. The results are satisfies the previous studies reported [14][15][16][17][18] .…”
supporting
confidence: 82%
“…This is the first kind of study performed to determine the anti-diabetic activity and standardizing dose of chitosan and chitooligosaccharides (chitin-based derivatives) in treatment of diabetes. The results are satisfies the previous studies reported [14][15][16][17][18] .…”
supporting
confidence: 82%
“…Nonetheless, the main drawbacks of acarbose are gastrointestinal effects including abdominal distention, flatulence, meteorism and possibly diarrhea, due to abnormal fermentation of undigested carbohydrates by colonial bacteria as a result of over inhibition of a-amylase (Jo et al, 2013). A more effective strategy in the control of T2DM involves a moderate a-amylase inhibition with a stronger inhibition on a-glucosidase.…”
Section: A-amylase and A-glucosidase Inhibition By Monoterpenesmentioning
confidence: 99%
“…Inhibition of these enzymes delays overall carbohydrate digestion and glucose absorption rate consequently blunting the increase of postprandial plasma glucose level. Thus, carbohydrate-hydrolyzing enzyme inhibitors such as acarbose, miglitol and voglibose have been clinically used as oral anti-hyperglycemic agents in the effective control of T2DM (Jo et al, 2013;Sugihara et al, 2014).…”
Section: A-amylase and A-glucosidase Inhibition By Monoterpenesmentioning
confidence: 99%
“…The chitosan particles bind with cholesterol and fatty acids to form clusters in the gastrointestinal tract, thereby reducing lipid absorption [20]. In addition to its effect on lipid absorption, chitosan has been described as reducing blood glucose levels and being capable of inhibiting the carbohydrate hydrolysing enzymes maltase, sucrose, and sucrose-isomaltase in the gut [21, 22]. …”
Section: Discussionmentioning
confidence: 99%